PREDICTIVE FACTORS ASSOCIATED TOWARDS QUALITY OF LIFE IN PATIENTS WITH CANCER: A CROSS-SECTIONAL STUDY - Rizka, Yulia; Deli, Hellena; Dewi, Wan Nishfa; Putriana, Nila (Nurse and Health: Jurnal Keperawatan, 2024)
Background: Cancer patients face various symptoms and problems caused by the disease or cancer treatment. Physical and psychological symptoms worsen the patient’s quality of life (QOL). Objectives: To predict how age, gender, marital status, educational level, working status, type of cancer, stage of cancer, physical factors (pain, fatigue, nausea, lack of appetite, shortness of breath, constipation, drowsiness, well-being) and psychological factors (anxiety and depression) affect to quality of life in patients’ cancer. Methods: The study was quantitative research with a cross-sectional approach with purposive sampling. Ninety-nine cancer patients participated in this study. Data were collected in General Hospital, Pekanbaru, in October - November 2022. The European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30) was used to assess patient’s cancer quality of life. The Multivariate analysis uses the multiple linear regression. Results: The EORTC QLQ-C30 mean scores for QoL (65,9725,18), physical, emotional and cognitive functioning were high, at 60 or above. The score of most symptom scales in this study were reportedly good, at 37 or below. However, for pain and fatigue, the score was reportedly worse (range:45, 3227,84 to 64,2725,58). The results of multiple linear regression analysis showed that factors predictive of quality of life were pain (p=0,032), fatigue (p=0,004), shortness of breath (p=0,020), constipation (p=0,002) and depression (p=0,042). These factors together can cause quality of life problems in cancer patients by 55% (adjusted R2 = 0.468). Conclusion: The study finding indicate that QoL score were influenced with several symptoms (pain, fatigue, shortness of breath, constipation and depression) of the ESAS-r score. Healthcare professionals should properly address pain and fatigue, as patients in this patient group consistently report them.